Almunisna Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Typhlocybini): a genus newly recorded from China with description of a new species - Huang, Min; Zhang, Yalin L. (Zootaxa, 2007)
The leafhopper genus Almunisna was described by Dworakowska (1969) with new species Almunisna bulbosa from Nepal as its type species. There have been no further reports on it. Here we record Almunisna from China for the first time based on A. bulbosa Dworakowska from Yunnan and a new species, A. quadratosa from Fujian, which we describe and illustrate. A key to separate males is presented. The type and observed specimens are deposited respectively in Chinese Agriculture University, Beijing (CAU), and Northwest A&F University, Yangling (NWAFU).